The Role of Spiritual And Psychological Factors In The Formation of A Folk Civil Servant - Kholiyarova Maxbuba Sottorovna (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article presents feedback on the factors that shape the spiritual and mental education of a folktale civil servant in the formation of a national personnel Corps, in which a civil servant, considered one of the main elements at the stage of transition to a social state, is able to solve the problems of citizens, provide moral and psychological support to citizens.